LIBERALISM AND DEMOCRACY IN THE PERSPECTIVE OF ISLAMIC EDUCATION - Marjuni Marjuni; Yuspiani Yuspiani; Alwan Suban (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:In the perspective of Islamic education, the concept of liberalism and democracy in education is about owning academic freedom, in which a lecturer can teach, and the students have the right to learn without limitation and mixing it with irrational thoughts. This paper aims to elaborate on the nature and the development of liberalism and democracy in Islamic higher education from different sources. The type of research used in this study was library research. The data were taken from various books and articles related to the topic then analyzed using content analysis. Based on the findings, the theory of the Islamic education philosophy about the concept of liberalism and democracy were so sustainable to provide possible solutions in education management, educational facilities, and infrastructure. Also, it could be a solution for educators to implement teaching methods or approaches that are more suitable for the learning process.Abstrak:Dalam perspektif pendidikan Islam, konsep liberalisme dan demokrasi dalam pendidikan adalah tentang memiliki kebebasan akademik, dimana seorang dosen dapat mengajar, dan mahasiswa berhak untuk belajar tanpa batasan dan mencampurkannya dengan pemikiran-pemikiran yang irasional. Makalah ini bertujuan untuk mengelaborasi sifat dan perkembangan liberalisme dan demokrasi di perguruan tinggi Islam dari berbagai sumber. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kepustakaan. Data diambil dari berbagai buku dan artikel yang berkaitan dengan topik tersebut kemudian dianalisis menggunakan analisis isi. Berdasarkan temuan tersebut, teori filosofi pendidikan Islam tentang konsep liberalisme dan demokrasi yang begitu lestari dapat memberikan solusi yang memungkinkan dalam pengelolaan pendidikan, sarana dan prasarana pendidikan. Selain itu, dapat menjadi solusi bagi pendidik untuk menerapkan metode atau pendekatan pengajaran yang lebih sesuai untuk proses pembelajaran.